A novel sequential electrostatic-HILIC SPE within a quantitative method for bivalirudin in human plasma by LC–SRM. (November 2016) - MacNeill, Robert; Acharya, Vishva; Patel, Neha; Parisi, Gregory; Katto, Kim; Lovich, Robert
Aim: This work set out to realize an idea for a novel means of extracting the peptide therapeutic bivalirudin from human plasma in what would be a uniquely selective means of SPE, a mixed-mode protocol involving electrostatic interactions followed by HILIC.Results: Inter and intra-assay relative error ranged from 3.52 to 8.23%, and 2.37 to 6.90%, respectively. Inter and intra-assay precision ranged from 2.64 to 7.12%, and 0.855 to 2.90%, respectively. Recoveries of 80% were attained, and there was no hint of discernible manifestation of matrix effects.Conclusion: The method was shown to perform excellently in the assessment tantamount to method validation. The essence of the extraction method presents a new option for highly selective extraction of peptides from biological matrices.